2013
DOI: 10.2215/cjn.09170912
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Des-acyl Ghrelin Levels with CKD

Abstract: SummaryBackground and objectives There are no effective therapies for malnutrition in CKD/ESRD patients. This study hypothesized that ghrelin, an endogenous orexigenic hormone, would correlate with renal function and might suggest therapeutic interventions for CKD/ESRD malnutrition.Design, setting, participants, & measurements Fifty-one CKD and 15 hemodialysis patients were enrolled. Acyl ghrelin (AG) and des-acyl ghrelin (DG) were determined using separate two-site-specific assays. Leptin, insulin, growth hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…We plan to clarify the effect of H. pylori eradication on ghrelin production in HD patients in the future; for this purpose, we will study H. pylori positive HD patients after eradication therapy. The des-acyl ghrelin level in patients with renal dysfunction is higher than that in subjects with normal renal function, as observed in this study [36] . In general, desacyl ghrelin has been considered an inactive form of ghrelin and to play non-biological roles, because of lack of binding capacity to conventional ghrelin receptor.…”
Section: Discussionsupporting
confidence: 81%
“…We plan to clarify the effect of H. pylori eradication on ghrelin production in HD patients in the future; for this purpose, we will study H. pylori positive HD patients after eradication therapy. The des-acyl ghrelin level in patients with renal dysfunction is higher than that in subjects with normal renal function, as observed in this study [36] . In general, desacyl ghrelin has been considered an inactive form of ghrelin and to play non-biological roles, because of lack of binding capacity to conventional ghrelin receptor.…”
Section: Discussionsupporting
confidence: 81%
“…Leptin increases with decreased renal function and is related to obesity and insulin resistance. In addition, one study reported that leptin and resistin are related in CKD patients 37 . A recent study also showed that leptin is significantly associated with FGF23 among patients on hemodialysis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin is a growth hormone-releasing peptide that regulates appetite, carbohydrate utilization, and insulin resistance. Ghrelin levels decrease with increasing renal function and are associated with mortality in CKD patients 37 . In the present study, the association between resistin and FGF23 remained significant even after adjusting for leptin and ghrelin.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for these seemingly contradicting findings is that only UAG levels were elevated in the CKD patients. For example, Gupta et al [18] analyzed AG and UAG levels in 51 CKD and 15 hemodialysis (HD) patients using two separate site-specific assays for these hormones. The results demonstrated that UAG levels increased with declining estimated glomerular filtration rate (eGFR), whereas AG levels remained unchanged.…”
Section: Ghrelin Obestatin and Ckdmentioning
confidence: 99%